The role of host eIF2α in viral infection - Yuanzhi Liu (Virology Journal, 2020)
Abstract Background eIF2α is a regulatory node that controls protein synthesis initiation by its phosphorylation or dephosphorylation. General control nonderepressible-2 (GCN2), protein kinase R-like endoplasmic reticulum kinase (PERK), double-stranded RNA (dsRNA)-dependent protein kinase (PKR) and heme-regulated inhibitor (HRI) are four kinases that regulate eIF2α phosphorylation. Main body In the viral infection process, dsRNA or viral proteins produced by viral proliferation activate different eIF2α kinases, resulting in eIF2α phosphorylation, which hinders ternary tRNAMet-GTP-eIF2 complex formation and inhibits host or viral protein synthesis. The stalled messenger ribonucleoprotein (mRNP) complex aggregates under viral infection stress to form stress granules (SGs), which encapsulate viral RNA and transcription- and translation-related proteins, thereby limiting virus proliferation. However, many viruses have evolved a corresponding escape mechanism to synthesize their own proteins in the event of host protein synthesis shutdown and SG formation caused by eIF2α phosphorylation, and viruses can block the cell replication cycle through the PERK-eIF2α pathway, providing a favorable environment for their own replication. Subsequently, viruses can induce host cell autophagy or apoptosis through the eIF2α-ATF4-CHOP pathway. Conclusions This review summarizes the role of eIF2α in viral infection to provide a reference for studying the interactions between viruses and hosts.